(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The work is devoted to the current theme, because in today’s socio-psychological insecurity in Ukraine there is no comprehensive approach to the organization of socio-psychological prevention of the consequences of psychotraumatic exacerbations of destructive aggression of servicemen who suffered in the conditions of participation in hostilities. The aim of the work is not only a theoretical analysis of the problem, but also a practical study of the current situation. This allows us to make conclusions and preventive recommendations, which in the future can be introduced into the professional practice of not only social workers, psychologists, but also commanders and rehabilitants. Therefore, the purpose of the study is to explore the main individual and psychological determinants of the formation of destructive aggressiveness and to develop on the basis of these appropriate directions of rehabilitation work to prevent it from servicemen. Empirical methods (observation, expert assessment of staff psychologists and commanders) were used for the study in order to identify soldiers who had destructive aggression after engaging in combat operations, interviewing, forming experiment, testing with psychodiagnostic techniques.The developed corrective program revealed a positive dynamics of personality changes that began to occur in the behavior of servicemen under the action of the measures taken. The training resulted in a significant decrease in physical aggression, a slight decrease in verbal aggression, a slight increase in indirect aggression. It is proved that the individual correction of consciousness and behavior of each serviceman inclined to aggressive actions, as well as the neutralization of negative interpersonal influences, provoking aggressive manifestations in the military. Such prevention can be carried out during a stressful situation, manifestation of aggression or after the end of an aggressive state. This program can be carried out during the service in part and after returning from the area of hostilities.